The use of coal ash from power plants as a soil conditioner - Sanga, Hilda Gerald (2019)
The disposal of coal ash, produced in large quantities by power plants as a by-product of coal combustion, is a significant environmental concern. Coal ash can be used as an agricultural soil conditioner because of its liming potential and the presence of many essential plant nutrients. However, recommendations for the agricultural use of coal ash should be based on sound knowledge of the coal ash characteristics, particularly the concentrations of potentially toxic elements (PTEs) in the ash. Due to the uptake of PTEs by crop plants it may pose risks to human health following the consumption of food crops.